Periodismo, experticia y toma de decisiones técnicas - Irarrázabal Elliott, Manuela (Pontificia Universidad Católica del Perú, 2021)
This paper addresses the problem of false balance in the press, in the context of technical decision making those in which science intersects with the public domain because the issues at stake are relevant for the population as a whole. It sets out to frame the problem in a broad context, the sociology of sciences, that enables meeting the need for recognising the democratic commitments of journalism and the importance of communicating technological progress efficiently to confront the challenges posed by misinformation. The methodology consists in a conceptual analysis, grounded in recent cases of false balance: climate change and vaccines. It concludes that the conceptual categories proposed by the theory help journalism regain a place of credibility where both the role of expertise and citizen participation find legitimacy in technical decision making, without blurring the distinction between the expert and the lay person.

Este artículo aborda el problema del falso balance en la prensa, en el contexto de la toma de decisiones técnicas aquellas en que la ciencia se interseca con el dominio político porque los temas en cuestión son relevantes para toda la población. El objetivo es enmarcar el problema en un contexto amplio, la sociología de las ciencias, que satisfaga la necesidad de reconocer los compromisos democráticos del periodismo y la importancia de comunicar los avances tecnológicos eficazmente y enfrentar la desinformación. La metodología consiste en un análisis conceptual, anclado en casos recientes de falso balance: cambio climático y vacunas. Se concluye que las categorías conceptuales propuestas por la teoría ayudan al periodismo a reconquistar un espacio de credibilidad en que se legitimen tanto la experticia como la participación ciudadana en la toma de decisiones técnicas, sin por ello difuminar la distinción entre la persona lega y la experta.
Journalism, Expertise, and Technical Decision-making
Keywords: sociology of sciences; expertise; media; democracy; technical decision-making; disinformation; Sociología de las ciencias; Experticia; Medios de comunicación; Democracia; Toma de decisiones técnicas; Desinformación; https://purl.org/pe-repo/ocde/ford#5.09.01